The participation of cyanobacteria in reducing the concentration of fusariotoxins and heavy metal ions in aqueous solutions (model experiments) - L. I. Domracheva; S. G. Skugoreva; A. I. Fokina; М. A. Zagoskin; Т. Ya. Аshikhmina (Юг России: экология, развитие, 2021)
Aim. The goal was to establish the effect of soil cyanobacteria (CB) Fischerella muscicola, Nostoc paludosum and Nostoc linckia on change in the concentration of heavy metal ions (HM) and fusariotoxins in aqueous media.Material and Methods. In order to plot the kinetics of sorption by dry biomass of CB Fischerella muscicola and Nostoc paludosum of copper(II), lead(II) and cadmium ions from solutions with a concentration of 10‐4mol/L, the method of potentiometry with ion‐selective electrodes was used. The concentration of fusariotoxins in the filtrate of the contact medium of Fischerella muscicola CB and Nostoc linckia with F. culmorumwas determined by HPLC.Results. The kinetics of sorption of TM ions by dry biomass of the CB isbest described by a modified second‐order model. According to the model, the sorption process limits the ion exchange reaction. In the presence of CB Fischerella muscicola and Nostoc linckia with a titer of 1.8∙106 cells/mL (1:100 dilution), a decrease in toxin and lycomarasmin in T‐2 medium occurs. However, this increases the concentration of fusaric acid and deoxynivalenol. In the variant where the titer of CB is equal to 1.8∙107cells/mL, the concentration of lycomarasmin is significantly reduced, while there is no change in the concentration of other fusariotoxins.Conclusion. Dry biomass of CB, having a high bisorption potential, can act as a good biosorbent with respect to copper(II), lead(II) and cadmium ions. A decrease in the concentration of fusariotoxins indicates the possibility of isolating active CB substances that can inhibit the biosynthesis of certain toxins of micromycetes of the genus Fusarium, reducing both the phytotoxicity of plant growth media and increasing the safety of crop production.